2014
DOI: 10.5194/acpd-14-24701-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An overview of regional and local characteristics of aerosols in South Africa using satellite, ground, and modeling data

Abstract: We present a comprehensive overview of particulate air quality across the five major metropolitan areas of South Africa (Cape Town, Bloemfontein, Johannesburg and Tshwane (Gauteng Province), the Industrial Highveld Air Quality Priority Area (HVAPA), and Durban), based on a decadal (1 January 2000 to 31 December 2009) aerosol climatology from multiple satellite platforms and detailed analysis of ground-based data from 19 sites throughout Gauteng Province. Satellite analysis was based on aerosol optical depth (A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 61 publications
(90 reference statements)
3
20
0
Order By: Relevance
“…They observed an average of 0.08 ( λ = 550 nm) over the Greater Cape Town area, which is ~0.090 at λ = 500 nm (using α 470–660 = 1.18). This value is somewhat more consistent with our value for continental air masses than Hersey et al 's [] study, although a precise comparison is hampered by different temporal and spatial scales. More interestingly, Kumar et al [] observed that the average AOD ( λ = 550 nm) for continental regions was fairly uniform at 0.07–0.08 except for most of the eastern half of South Africa and the Kalahari Desert, reaching ~0.12.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…They observed an average of 0.08 ( λ = 550 nm) over the Greater Cape Town area, which is ~0.090 at λ = 500 nm (using α 470–660 = 1.18). This value is somewhat more consistent with our value for continental air masses than Hersey et al 's [] study, although a precise comparison is hampered by different temporal and spatial scales. More interestingly, Kumar et al [] observed that the average AOD ( λ = 550 nm) for continental regions was fairly uniform at 0.07–0.08 except for most of the eastern half of South Africa and the Kalahari Desert, reaching ~0.12.…”
Section: Resultssupporting
confidence: 91%
“…Monthly AOD averages ranged from~0.15 (λ = 558 nm) in September to~0.07 in June with an annual average~0.10. Hersey et al [2014] examined AOD from 2000 to 2009 at five major metropolitan regions of South Africa, including the Greater Cape Town area. The annual cycle in AOD determined from MODIS and MISR had identical features to the cycle at CPT in Figure 6.…”
Section: Ground Versus Satellite-based Aod At Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…It is pertinent to first note that the intercomparison between columnar spaceborne aerosol data and surface in situ measurements requires caution due to the different spatial fingerprints of the two types of data. When assuming that the intercomparison is fair to do, it was shown for the greater Tehran area [ Crosbie et al ., ] and South Africa [ Hersey et al ., ] that differences in temporal profiles between AOD and surface PM are due to lower PBLHs concentrating PM in a smaller volume of air leading to higher surface PM, whereas columnar AOD is immune to this issue. In our study region when PBLH is lowest (September–December), the surface PM concentrations exhibit the full range of levels including the minimum (September) and maximum (December) mean value for the entire year.…”
Section: Discussionsupporting
confidence: 62%
“…Discrepancies between total column AOT and surface estimates of particles (dry mass + ALW) are noted in the literature and are often consequences of complex aerosol vertical structure [ Hersey et al ., ]. For example, particle plumes aloft may enhance AOT but not impact surface measurements [ Campbell et al ., ], as suggested by Ford and Heald, while high PM concentrations in a shallow boundary layer with particle‐free air aloft can have a “low” AOT retrieval [ Crosbie et al ., ].…”
Section: Resultsmentioning
confidence: 99%